(3GdJPjjd hGdJPfjH Ydi fgGjI GdZQjHs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi djS deYdheGJg fgGjI CeG HYO aEf GdfgGjI ai ZQjH GdMOjK ddEeGe GHf GdCKjQ CLd cJGH Cda ai GdZQjH s
(3BNQgG (B:s
(3GdehGQHI hGdeOGgGI hGdebGJdI aGdXGgQ Cf GdeQGO cGf efge eNGOYI HGXgGQ GdESdGe hHGWfge HNdGag s
(3hQO GdYfhGf GdCUdi ai cX (B2 / 1206s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(2 / 9835) s
Keywords: (3GddZIs